The Economics of Urban Slaveholding in Santiago, Chile, 1773-1810 - Martinez-Barraza, J (Cambridge University Press, 2021)
This paper applies modern economic theory to the ownership of enslaved men and women in the labour market context of Santiago, Chile from 1773 to 1810. We calculate the internal rate of return for slaves by gender and age as a way to understand the economic justification of slavery in an urban scenario where free labour was also readily available. Based on archival sources documenting the selling prices for slaves, prevailing wages for free labourers, maintenance costs and life expectancy, we argue that the ownership of enslaved men and women was a consistently profitable activity. Copyright © Instituto Figuerola, Universidad Carlos III de Madrid, 2020.